The Big Three and board gender diversity: The effectiveness of shareholder voice - Gormley, Todd A.; Gupta, Vishal K.; Matsa, David A.; Mortal, Sandra C.; Yang, Lukai (Journal of Financial Economics, 2023)
In 2017, “The Big Three” institutional investors launched campaigns to increase gender diversity on corporate boards. We estimate that their campaigns led American corporations to add at least 2.5 times as many female directors in 2019 as they had in 2016. Firms increased diversity by identifying candidates beyond managers’ existing networks and by placing less emphasis on candidates’ executive experience. Firms also promoted more female directors to key board positions, indicating firms’ responses went beyond tokenism. Our results highlight index investors’ ability to effectuate broad-based governance changes and the impact of investor buy-in in increasing corporate-leadership diversity.